Sclerotic ostitis in jaw bones in Iraqis (A radiographic study) (Mustansiria Dental Journal, 2018)
The objective of this study was to investigate the frequencies of sclerotic ostitis injaw bones in Iraqi patient population with respect to age and gender, in addition toshape, localization, and the dental relationship of lesions.A retrospective study was performed using a conventional panoramic radiographsof 867 patients ranging in age from 15 to 60 years subjected to dental treatment.Descriptive characteristics of radiopacities (Idiopathic osteosclerosis IO, andCondensing ostitis CO) including shape, location, and its dental relationship wererecorded.There were 40 radiopacities detected, 27 IO lesions in 24 subjects (3.1 %) (15females, 9males), and 13 CO lesions in 11 subjects (1.2 %) (9 females, 4 males). BothIO and CO lesions were found to be higher in number among females when comparedto males. The frequency of IO lesions was found to be significantly higher in the agegroup (31-45 years) than in other groups. On the other hand, the frequency of COlesions was higher in both age groups (31-45) and (46-60), and its frequency in theseperiods was statistically higher than in the (15-30).Our results point to the low IO and CO frequency among the Iraqi population. Inaddition, our findings support the theory that IO lesions are developmental variationsof normal bone architecture unrelated to a local stimulant and CO lesions could beconsidered reactive formations related to teeth with severe caries,restoration, orpulpitis.